3D and 2D experimental views on the flow field of gas-evolving electrode cold model for electrolysis magnesium. (October 2015) - Liu, Chenglin; Sun, Ze; Lu, Guimin; Song, Xingfu; Yu, Jianguo
Abstract: In the magnesium electrolysis process, chlorine gas bubbles release at the surfaces of anode and affect electrolyte flow patterns. This paper presents an experimental apparatus to simulate the flow field induced by chlorine gas evolution at the gas-evolving electrodes of magnesium electrolysis cell. The three-dimensional flow structures were determined by using volumetric three-component velocimetry (V3V) technique, which has the ability to capture the out-of-plane velocity component. The three-dimensional flow structures in the region with a depth about 120 mm can be obtained. To achieve this, approximately 15, 000 three-dimensional velocity vectors were detected in the flow measurements and constituted the three-dimensional flow field, which eliminated the perspective error caused by the out-of-plane motion in Particle Image Velocimetry (PIV) method. In experiments, comparisons are made between the V3V and PIV results. The in-of-plane velocities data obtained by V3V technique have the same trend with the PIV results, and V3V provides more details in the third direction for the flow field accurately.